Perioperative Delirium: A Literature Review of Management in Intensive Care Unit - Cendy Legowo (Open Access Indonesian Journal of Medical Reviews, 2021)
Perioperative delirium is a wide-ranging problem that directly affects primary clinical results. Delirium is an organ dysfunction in critically ill patients, independently associated with improved morbidity. This review aimed to explain perioperative delirium and its management in the intensive care unit. Most cases of delirium in the ICU remain undiagnosed. The delirium assessment is only for patients who respond to sound; therefore, it is necessary to use sedatives or disturbance of consciousness; the approved scale is the Richmond restless sedation scale (RASS) or the sedative restlessness scale (SAS). In a clinical setting, the diagnosis of postoperative delirium can be challenging. Delirium may manifest as agitation (hyperactivity) or withdrawal (hyperactivity), often alternating significantly. Formal neurocognitive assessments are very time-consuming and are usually only used by experts. The first-line treatment of postoperative delirium is evaluating and treating the underlying cause. In conclusion, delirium will increase the responsibility of many doctors with the ability to avoid precipitation factors. Efficient treatment, differences between engine subtypes, and the long-term results of delirium in ICU require additional investigation.